Management of Recurrent Aphthous Stomatitis in a Patient with High Recurrence Frequency - Sri Hernawati (Humanistic Network for Science and Technology (HNST), 2020)
RAS (Recurrent Aphthous Stomatitis) is an inflammation of soft tissues of the oral cavity characterized by recurrent and painful ulcers. These lesions can be marked early on with a burning sensation, and when the wound has formed, the pain is getting worse. Occasional symptoms of precursors, paresthesia and hyperesthesia, are sometimes reported. Pain and discomfort arise along movement around the ulcer e.g. eating, talking and swallowing. Characteristics of RAS are usually single or multiple ulcers occurring recursively on the oral mucosa, round or oval in shape, clearly demarcated, with a grayish-yellow necrotic center and reddish edges. Lesions occur at young ages i.e. children and puberty, and may occur in adults as well. Ulcers usually last in 1 week or month. This disorder is classified into three categories according to size i.e. recurrent aphthous stomatitis minor, major and herpetiformis. The aim of this report is to show the management of cases of Recurrent Aphthous Stomatitis Minor on the left side of tongue, left buccal mucosa, and lower labial mucosa in female patient aged 19 years. A 19-year-old female patient came to the Dental Hospital of Jember University with complaints of thrush on the left side of her tongue, left buccal mucosa and lower labial mucosa, pain, and feeling disturbed due to the pain when eating, talking, and laughing. In this case, the diagnosis showed Recurrent Aphthous Minor Stomatitis on the left side of the tongue, left buccal mucosa, and lower labial mucosa. The therapy was using nonsteroidal anti-inflammatory mouthwash containing aloe Vera and hyaluronic acid as well as giving multivitamin of becomzet (vitamin B complex, A, C, E, and Zinc). Keywords: recurrent aphthous stomatitis; high recurrence